Self-implantable double-layered micro-drug-reservoirs for efficient and controlled ocular drug delivery - Than, Aung; Liu, Chenghao; Chang, Hao; Duong, Phan Khanh; Cheung, Chui Ming Gemmy; Xu, Chenjie; Wang, Xiaomeng; Chen, Peng (Nature communications, 2018)
Eye diseases and injuries impose a significant clinical problem worldwide. Safe and effective ocular drug delivery is, however, challenging due to the presence of ocular barriers. Here we report a strategy using an eye patch equipped with an array of detachable microneedles. These microneedles can penetrate the ocular surface tissue, and serve as implanted micro-reservoirs for controlled drug delivery. The biphasic drug release kinetics enabled by the double-layered micro-reservoirs largely enhances therapeutic efficacy. Using corneal neovascularization as the disease model, we show that delivery of an anti-angiogenic monoclonal antibody (DC101) by such eye patch produces ~90% reduction of neovascular area. Furthermore, quick release of an anti-inflammatory compound (diclofenac) followed by a sustained release of DC101 provides synergistic therapeutic outcome. The eye patch application is easy and minimally invasive to ensure good patient compliance. Such intraocular drug delivery strategy promises effective home-based treatment of many eye diseases. Treatment for eye injuries and diseases is most efficient when delivered directly into the eye. Here, the authors developed a patient-friendly eye patch equipped with an array of detachable microneedles, through which drugs can be delivered through the cornea for an extended period of time.